2014
DOI: 10.5039/agraria.v9i2a3518
|View full text |Cite
|
Sign up to set email alerts
|

Atividade respiratória como teste de vigor em sementes de algodão

Abstract: RESUMOVários testes de vigor são utilizados atualmente pelas empresas produtoras de sementes para avaliar a qualidade dos lotes. Entretanto, nem sempre esses testes se relacionam com a emergência de plântulas no campo e possuem desvantagens, como a demora na obtenção de resultados. O trabalho teve o objetivo de avaliar a eficiência da atividade respiratória como teste de vigor em sementes de algodão. Os experimentos foram conduzidos no ano de 2012, em laboratório e em casa de vegetação. Foram utilizadas sement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Overall, the respiratory activity test was correlated with the physiological quality of seeds, and therefore, could potentially be used to quickly estimate the quality, consistent with results found for cotton seeds (VENSKE et al, 2014), soybean seeds (MENDES et al, 2009) and sunflower seeds (DODE et al, 2012).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Overall, the respiratory activity test was correlated with the physiological quality of seeds, and therefore, could potentially be used to quickly estimate the quality, consistent with results found for cotton seeds (VENSKE et al, 2014), soybean seeds (MENDES et al, 2009) and sunflower seeds (DODE et al, 2012).…”
Section: Resultssupporting
confidence: 80%
“…On the other hand, the length of the root had a lower correlation (r = -0.59). Dode et al (2013) and Marini et al (2013) also showed a negative correlation between respiration and vigor for sunflower and rice seeds, respectively, which can be explained by the fact that seeds in an advanced process of decay have a higher metabolism, possibly seeking to reorganize its cellular machinery in order to increase respiratory activity (VENSKE et al, 2014). In watermelon seeds, Oliveira et al (2015) found that the respiratory activity allowed the separation of seeds lots, but there were no positive or significant correlations with other vigor tests.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Castro (2011) observed this differentiation in maize seeds; Pereira (2012) in pepper and chili seeds; Dranski et al (2013), in canola seeds and Venske et al (2014) in cotton seeds. By the titulation method, it was also possible to separate statically the five lots of maize seeds in three levels of vigor.…”
Section: Resultsmentioning
confidence: 99%